The Effectiveness of Contralateral C7 Nerve Root Transfer for the Repair of Avulsed C7 Nerve Root in Total Brachial Plexus Injury: An Experimental Study in Rats - Lin, Haodong; Sheng, Jun; Hou, Chunlin (Journal of Reconstructive Microsurgery, 2013)
The aim of this study was to evaluate the feasibility and effectiveness of transferring the contralateral C7 root to repair avulsed C7 nerve root. Thirty rats were randomized into three groups. In group A, rats underwent whole-root avulsion of the left brachial plexus and contralateral C7 root transfer to the avulsed C7 nerve root. In group B, rats underwent whole-root avulsion and contralateral C7 root transfer to the radial nerve. In group C, rats underwent whole-root avulsion of the left brachial plexus without nerve transfer. Functional outcomes were measured by electrophysiological studies, muscle tetanus contraction force, muscle mass, and histology. Six months postoperatively, increased amplitude and shortened latency of compound muscle action potentials, larger maximum tetanic contractile tension, heavier muscle mass, and larger cross-sectional area of the muscle fibers were observed in the triceps, extensor carpi radialis brevis, and extensor digitorum in groups A and B when compared with group C (p < 0.01). There were no significant differences between group A and B (p > 0.05). Contralateral C7 nerve transfer to repair avulsed C7 nerve root was feasible and effective in this rat model. It should be considered as an option for the treatment of brachial plexus injuries.
Keywords: nerve transfer; contralateral C7; brachial plexus; radial nerve